Frigg’s Cunning: Initiation in the Framing Myth of Grímnismál - Kure, Henning Haglskær (Religionsvidenskabeligt Tidsskrift, 2022)
SUMMARY: This article applies the initiation model, developed by Jens Peter Schjødtas a tool to identify themes of initiation in Old Norse myths, to the prose introductionof the eddic poem Grímnismál. After having introduced Schjødt’s initiation model, thearticle contextualises the prose introduction within the themes of the myth found in thepoem; then, it applies the initiation model to the prose text’s figures of Geirrøðr andAgnarr; and, lastly, it focusses on the cunning role of Frigg in the prose. This leads tothe suggestion that the myth that frames Grímnismál may be a story aboutcontextualizing war and warrior ways in a society of peace, with initiation as an idealtool of ’civilizing’ the ruling powers. RESUME: Denne artikel anvender initiationsmodellen, udviklet af Jens Peter Schjødtsom et værktøj til at identificere initiationstematikker i norrøne myter, påprosaintroduktionen af eddadigtet Grímnismál. Efter at have introduceret Schjødtsinitiationsmodel, kontekstualiserer artiklen prosaintroduktionen inden for de mytisketemaer, der findes i digtet, dernæst anvender den initiationsmodellen på prosatekstensfigurer Geirrøðr og Agnarr og slutteligt fokuserer den på Friggs listige rolle i teksten.Dette leder til forslaget, at myten, der omrammer Grímnismál, kan være en fortællingom at kontekstualisere krig og krigeres adfærd i et samfund bygget på fred medinitiation som et ideelt værktøj til at ‘civilisere’ de herskende magter.